Analisis Kelayakan Pendanaan Pembangkit Listrik Energi Baru Terbarukan (EBT) di Sulawesi Barat - Alyaa Ashiilah Setiawan; Tantina Haryati (Universitas Batanghari Jambi, 2023)
This study aims to analyze the investment attractiveness of New Renewable Energy (NRE) power plants in West Sulawesi, which currently has not attracted the attention of investors to replace PLTU in the biomass sector with factors that influence investors in making investment decisions including capital budgeting factors. This study uses a qualitative research approach. The research method used is phenomonology in the form of an analysis of the attractiveness of investment in the development of the NRE electricity sector in West Sulawesi. Based on the results of the analysis, it can be concluded that the investment attractiveness of New, Renewable Energy (NRE) in West Sulawesi is quite attractive in the eyes of foreign investors, but there are obstacles that hinder the negotiation process, namely regulations that are less detailed in the pricing system for NRE generation. So it is necessary that capital budgeting method has an important role in influencing investor decisions in investment decisions.